2009
DOI: 10.1136/jnnp.2008.155291
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of independent bitemporal lobe epilepsy defined by invasive recordings

Abstract: Surgical resection is an important treatment option for medically intractable bitemporal epilepsy. The proportion of seizures arising from one temporal lobe is not reliable as a single indicator to prognosticate the results of surgery on seizure tendency. In addition, individuals who achieved only palliation by reducing seizure frequency experienced improvement in quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 33 publications
3
36
1
2
Order By: Relevance
“…However, on a descriptive level, the surgical group reported a slightly better subjective outcome on most questionnaires. Surgical patients reported a significant improvement in quality of life (QOLIE-10) after surgery, as was also found by Boling et al 6 The mean score at follow-up, however, still indicated an impaired quality of life. Regarding depressed mood, both groups were comparable at baseline.…”
Section: Figsupporting
confidence: 79%
See 1 more Smart Citation
“…However, on a descriptive level, the surgical group reported a slightly better subjective outcome on most questionnaires. Surgical patients reported a significant improvement in quality of life (QOLIE-10) after surgery, as was also found by Boling et al 6 The mean score at follow-up, however, still indicated an impaired quality of life. Regarding depressed mood, both groups were comparable at baseline.…”
Section: Figsupporting
confidence: 79%
“…46 In contrast, stable (although severely impaired) postoperative memory functions were reported in a noncontrolled study. 8 Finally, a predominantly favorable subjective outcome has been described by Boling et al 6 in 11 patients with bilateral TLE, 3 of whom had bilatNeuropsychological outcome after epilepsy surgery in patients with bilateral Ammon's horn sclerosis eral AHS. While 7 patients reported an improved quality of life, subjective memory was unchanged in 8 patients.…”
Section: ©Aans 2014mentioning
confidence: 91%
“…HFO-generating regions identified SOZ with greater specificity and accuracy compared with that of the spike-generating regions [9,27]. Furthermore, some studies indicated that removal of the HFO-generating region predicted better surgical outcome [10][11][12][13]. These studies suggested that HFOs appeared to be reliable biomarkers of SOZ.…”
Section: Identification Of Sozmentioning
confidence: 88%
“…Reports over the last decade on human epileptic brain with intracranial recording have suggested that HFOs are linked to epileptogenic zones [6,7,9,10]. Studies the removal of HFO-generating areas rather than spike-generating areas [10][11][12][13]. Furthermore, the use of HFOs as biomarkers of epileptogenicity in resective procedures improves seizure outcome and represents a novel approach for the treatment of epilepsy.…”
Section: Introductionmentioning
confidence: 98%
“…Bitemporal epilepsy has been defined by depth electrodes, as clear clinical and scalp EEG differences that could noninvasively distinguish bitemporal epilepsy from unilateral temporal lobe epilepsy have not been established [1]. Patients with bitemporal epilepsy are generally considered to be poorer surgery candidates than patients with unilateral temporal lobe epilepsy [2][3][4][5]. Seizure semiology is an important part of the presurgical assessment of epilepsy surgery candidates.…”
Section: Introductionmentioning
confidence: 99%